Building a stronger and more integrated Europe - Caldera Sánchez, Aida (OECD Economics Department Working Papers, 2018)
Europe's economy is finally growing robustly. These positive developments provide an opportunity to renew efforts to meet the long-term challenges facing the European Union (EU). The EU's record on reducing regional income disparities is mixed and this explains some of citizens' discontent with the European project. Reforming cohesion policy by focusing spending more on items with long-term growth benefits and clear spillovers across borders, including human capital and infrastructure investment could further support income convergence. Higher co-funding rates and less burdensome administration of the cohesion and structural funds could encourage greater spending effectiveness. Sustained improvements in living standards are held back by weak productivity and investment in many countries. Reviving the single market project, by removing remaining barriers in services, energy, digital and transport can help to spur long-term growth. Deepening the single market and faster adoption of digital technologies will create new jobs but put at risk others, perhaps in lagging regions. The EU can help lagging regions catch up by reforming cohesion policy and facilitating firm creation through the removal of barriers across the single market. It can also support better those who lose out from globalisation and are displaced by technological change by making access to the European Globalisation Adjustment Fund easier and broadening its scope not only to help workers displaced by globalisation or an economic crisis, but also due to other reasons such as automation. This Working Paper relates to the 2018 OECD Economic Survey of the European Union. (http://www.oecd.org/eco/surveys/economic-survey-european-union-and-euro-area.htm)